Probing the electron–phonon interaction in superconductivity for KSn2 using the Migdal-Eliashberg theory and linear-response theory. (2nd January 2020) - Saib, S.; Karaca, Ertuǧrul; Uzunok, H. Y.; Tütüncü, H. M.; Srivastava, G. P.
ABSTRACT: We have studied the structural and electronic properties of potassium distannide KSn 2 crystallizing in the MgZn 2 -type (C14) Laves structure by employing the generalised gradient approximation of the density functional theory and the plane wave ab initio pseudopotential method. It is found that the bonding character in this system is a mixture of covalent, ionic and metallic bonds. The stress–strain method calculations confirm the mechanical stability, and the phonon dispersion results with real frequencies reveal the dynamical stability of the structure. The electron–phonon interaction has been investigated by using the linear response approach and the Migdal-Eliashbergh approach. The integration of the Eliashbergh spectral function gives the value of average electron-phonon coupling parameter to be of the weak strength 0.637. The superconducting temperature is obtained to be 2.7 K, which is in good accordance with its measured value of 3.2 K.